El caso Schönborn: un cambio retórico en la postura católica ante la evolución biológica - Díaz Rojo, José Antonio ('Ilu. Revista de Ciencias de las Religiones, 2009)
The objective of this paper is to make a rhetorical analysis of the op-ed entitled «Finding Design in Nature» by Cardinal Christoph Schönborn, Archbishop of Vienna, published by The New York Times in 2005, three months after the death of John Paul II. In this essay, the Cardinal states that it is an error to affirm that Catholic doctrine is compatible with the «neo-Darwinist» theory of evolution and that the Roman Catholic Church accepts that theory. For the Archbishop, the origin of this error lies in the abuses committed in the interpretation of John Paul’s 1996 speech in which the Pope affirmed that evolution was more than a hypothesis and showed himself more favourable towards evolutionary theory than his predecessors. In his article the Cardinal described that papal message as «vague and unimportant». In this paper, the rhetorical techniques used by Schönborn in his article are analysed: the lexical choices to make a negative assessment of «neo Darwinist» evolutionary theory; the argumentative definition to make a polemical description of that theory; and the polyphonic proceedures designed to decontextualise the papal discourse and present Catholic beliefs as the truth. We interpret Cardinal Schönborn’s position as a rhetorical change with respect to John Paul II’s 1996 speech. From our point of view, the Archbishop directed his criticism against evolutionary theory not only because of its scientific theories (not rejected by Church teaching) but also for being potentially dangerous in its use by certain authors as a scientific argument in defence of their atheism.
Keywords: Rhetoric; Evolutionaty theory; Catholic doctrine; Cardinal Schönborn; John Paul II